Consumer Valuation of Driving Range: A Meta-Analysis - Alexandros Dimitropoulos; Piet Rietveld; Jos N. van Ommeren (Tinbergen Institute, 2011)
We perform a meta-analysis of studies investigating consumers' preferences for electric and other alternative fuel vehicles to provide insights into the way consumers trade off driving range for capital costs. We find that consumers are willing to pay, on average, between 47 and 64 USD for a one-mile increase in vehicle's range. The short driving range of most currently available electric vehicles entails that they should be offered at prices around half the price of their conventional counterparts in order to be considered competitive alternatives, ceteris paribus. In line with intuition, but in contrast to most specifications employed in primary studies, we find evidence that consumers' marginal willingness to pay (WTP) is decreasing in driving range. The wide divergence in the estimates of welfare measures among the examined studies can be mainly attributed to differences in the study design, the location at which the study was conducted and the size of the study's sample. Provided that a large scale introduction of electric vehicles is a policy aim, our findings support the continuation of R&D efforts directed towards the reduction of battery costs and the development of advanced battery technologies permitting higher driving ranges than the ones currently achievable by most commercially available electric cars.
urn:NBN:nl:ui:31-1871/38543
Keywords: R41; D12; Q41; Q42; 330; Electric vehicles; Meta-analysis; Driving range; Willingness to pay